Health information seeking in the digital age: an analysis of health information seeking behavior among US adults - Jacobs, Wura (Cogent social sciences, 2017)
We live in a digital age and this has changed the landscape of health information. With the changing US demographic, otherwise acute diseases morphing into chronic diseases as a result of treatment advancements, and evolving health needs of the population, there is need for increase in available and accessible health information. It is estimated that one in three US adults use the internet to diagnose or learn about a health concern. Nevertheless, a nagging question is whether the Web is reducing or creating disparities in health information availability and use for making health decisions. This study examined factors associated with heath information seeking from the internet, traditional media, and health care professionals among a diverse population of US adults. Data for the analysis was from four cycles (2011-2014) of the Health Information National Trends Survey (HINTS), a national survey of US adults. Controlling for age, race/ethnicity, gender, and socioeconomic status (SES), regression analyses were conducted. STATA 13 was used for analyses. Findings indicated that there is a possibility that while the Web is an easily available source of health information, it could also create inequalities in health information accessibility. The Web should not be considered a substitute for using alternative health information sources. Doing so, might create disproportionate access to health information essential for health decisions.